Companion Proceedings of the XIV Brazilian Symposium on Multimedia and the Web 2008
DOI: 10.1145/1809980.1810057
|View full text |Cite
|
Sign up to set email alerts
|

Automatic summarization for text simplification

Abstract: In this paper we present experiments on summarization and text simplification for poor readers, more specifically, functional illiteracy readers. We test several summarizers and use summaries as the basis of simplification strategies. We show that each simplification approach has different effects on readers of varied levels of literacy, but that all of them do improve text understanding at some level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Some efforts have been made on summarisation as simplification. Margarido, Pardo, Antonio, Fuentes, Aires, Aluísio, and Fortes (2008) tested three different extraction-based summarisation strategies on target readers, and found that all strategies improved the understanding of the text to some extent. They concluded that summarisation, in combination with other techniques, could be useful for simplifying texts, but that it is important to take the literacy level of the reader into account.…”
Section: Automatic Text Summarisationmentioning
confidence: 99%
“…Some efforts have been made on summarisation as simplification. Margarido, Pardo, Antonio, Fuentes, Aires, Aluísio, and Fortes (2008) tested three different extraction-based summarisation strategies on target readers, and found that all strategies improved the understanding of the text to some extent. They concluded that summarisation, in combination with other techniques, could be useful for simplifying texts, but that it is important to take the literacy level of the reader into account.…”
Section: Automatic Text Summarisationmentioning
confidence: 99%
“…The advances in computer vision means that multimodal summarisation is more feasible now, with systems that are able to caption images (Tanti, Gatt, and Camilleri, 2018) or are able to summarise complex sentences with images and other graphical representations (UzZaman, Bigham, and Allen, 2011). Methods from automatic summarisation also proved useful for text simplification (Margarido, Pardo, Antonio, Fuentes, Aires, Aluísio, and Fortes, 2008).…”
Section: Orȃsanmentioning
confidence: 99%
“…It is an open-source application to generate multilingual extractive summaries that can be downloaded online. 7 This tool allows constructing extractive summaries based on the detection of the main ideas from the source document, considering the reduction of redundant information.…”
Section: Open Text Summarizer (Ots)mentioning
confidence: 99%
“…Since 1993, the researchers of NILC and others have been performed several applications for Portuguese ATS. Some of them include the use of supervised and unsupervised machine learning methods [1,2], discursive knowledge models [3][4][5], identification of "gist sentence" from the source documents to generate extractive summaries [6], Text Simplification (TS) [7], complex networks and graph-based methods to text analysis [8][9][10][11]. On the other hand, some ATS systems have been proposed to generate extractive summaries through optimization-based methods [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%